2021
DOI: 10.3389/fpubh.2021.674035
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Social Needs Among Chinese American Primary Care Patients During the COVID-19 Pandemic: Implications for Cancer Screening and Primary Care

Abstract: Research Objective: Initiatives to address social determinants of health (SDOH) and measure health-related social needs (HRSN) within clinic settings are increasing. However, few have focused on the specific needs of Asian Americans (AA). We examine the prevalence of HRSN during a period spanning the COVID-19 pandemic to inform strategies to improve cancer screening and primary care among AA patients.Methods: We implemented a self-administered HRSN screening tool in English and Chinese, traditional (T) or simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Participants completed the survey on a computer tablet before, during, or after their clinic visit. The survey consisted of the 10-item Accountable Health Communities (AHC) health-related social needs screening tool, which is widely used and includes questions on housing, food, transportation, utilities, and interpersonal violence; 2 outcome measures of acceptability; and 20 questions on social risk factors associated with patient acceptability (eAppendix in Supplement 1). We modified questions from an earlier study evaluating acceptability of social risk screening in primary care clinics and EDs for use in a dermatology clinic setting.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed the survey on a computer tablet before, during, or after their clinic visit. The survey consisted of the 10-item Accountable Health Communities (AHC) health-related social needs screening tool, which is widely used and includes questions on housing, food, transportation, utilities, and interpersonal violence; 2 outcome measures of acceptability; and 20 questions on social risk factors associated with patient acceptability (eAppendix in Supplement 1). We modified questions from an earlier study evaluating acceptability of social risk screening in primary care clinics and EDs for use in a dermatology clinic setting.…”
Section: Methodsmentioning
confidence: 99%
“…Health The entire AHC tool has also applied to studies of diverse communities including English and Chinese versions which were self-administered to Asian Americans during COVID-19 to inform cancer screening and primary care (Tsui et al, 2021). However, initial validation of the tool has not been tested as a whole, but questions come from a range of expert domain-specific sources with supporting psychometric properties (Centers for Medicare and Medicaid Services et al, 2017).…”
Section: Protocol For Responding To and Assessing Patient Assets Risk...mentioning
confidence: 99%
“…It is unclear whether access to HPV vaccine information and limited knowledge about HPV vaccines persists as a key barrier to vaccine uptake among immigrant parents living in surburban, higher socioeconomic areas. Prior studies in suburban communities have shown that while these areas have higher unadjusted access to health care overall, a large proportion of surburban residents lack access to health care and remain medically vulnerable [ 13 , 14 ]. Studying this population may provide a better understanding of why HPV vaccine knowledge and HPV vaccine uptake remain lower in New Jersey compared to neighboring metropolitan areas such as Philadelphia and New York City [ 15 ] despite having higher education and socioeconomic status at the population level.…”
Section: Introductionmentioning
confidence: 99%